Electrochemical and Scanning Force Microscopy Characterization of Fractal Palladium Surfaces Resulting from the Electroreduction of Palladium Oxide Layers - Kessler, Teresita (1996)
Pd oxide layers were grown by applying to smooth Pd electrodes a potential reversal technique (PRT) in 1 M H2SO4 at 25 °C. The electroreduction of the Pd oxide layer was made either voltammetrically or potentiostatically, yielding a Pd overlayer with a large increase in surface area. The effective range of PRT conditions for increasing the Pd surface area was established. The increase in surface area of treated Pd was voltammetrically determined. The electrochemical behavior of treated Pd electrodes in acid revealed an enhancement of the H atom surface electroadsorption processes. This behavior is consistent with the fractal characteristics of the treated Pd electrode surface, as demonstrated by the analysis of scanning force microscopy imaging data.